HOW DOES E-LEARNING HELP THE ACHIEVEMENT OF IQF? THE ANALYSIS OF E-LEARNING TASK OF CREATING TEMPORAL EVOLUTION CHART AND THE ABILITY TO SOLVE THE PROBLEMS IN THE SYMPTOMS OF VIBRATIONS AND WAVES - Widodo, Wahono; Rosdiana, Laily; Nurita, Tutut; Fauziah, An nuril Maulida (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
The use of e-learning to improve students' ability in using technology to help solve the problem (Level 6 Indonesia Qulaification Framework, IQF) is challenging. This study aimed to describe the use of e-learning to improve students' ability to create charts of the evolution of the spatial and temporal regions of the symptoms of vibrations and waves by using a computer, problem solving skills, as well as the responses of students prospective science teachers to use e-learning to the symptoms of vibrations and waves. This research is a quasi-experimental design with one shot case study, with 28 research subjects science student teachers semester 5. Treatment in the form of learning materials, learning, performance tasks, and test essay on e-learning system Unesa (www.vilearn.unesa.ac.id). The ability to make charts the evolution of the spatial and temporal with computers and the ability to solve problems is measured using an appropriate rubric, student responses obtained through the questionnaire. The results showed, with the provision of sustainable performance tasks on e-learning followed up with feedback, students' ability to make a graph of spatial temporal evolution of the computer and problem solving skills have increased. A total of 85.7% of the students stated that create the spatial and temporal evolution chart using a computer is difficult, but 67.9% of them stated that the e-learning to assist them in making a graph. A total of 100% of the students have the ability to solve the problems above minimum standards, with an average value of 82.9, which shows the use of e-learning helps students to master solving problems on vibrations and waves.